Controle químico de plantas dos gêneros Ipomoeae Merremia em cana-soca - Correia, N. M. [UNESP] (2010)
To evaluate the efficiency of herbicide application in post emergence, alone and in mixture, for Ipomoea grandifolia, I. hederifolia, I. purpurea, I. quamoclit, Merremia aegyptia and M. cissoides control in sugarcane, an experiment was conducted on a commercial production area in Jaboticabal, SP, Brazil, from November 2007 to July 2008. Six herbicide treatments [trifloxysulfuron plus ametryn (37 plus 1463.07 g ha(-1)), diuron plus hexazinone (1.170 + 330 g ha(-1)), metribuzin (1.920 g ha(-1)), (trifloxysulfuron plus ametryn, 27.75 + 1097.3 g ha(-1)) plus (diuron plus hexazinone, 702 + 198 g ha(-1)), metribuzin (960 g ha(-1)) plus (trifloxysulfuron plus ametryn, 27.75 + 1097.3 g ha(-1)) and metribuzin (960 g ha(-1)) plus (diuron plus hexazinone, 702 + 198 g ha(-1))] and two treatments without application were evaluated. The visual injuries caused by the herbicide did not affect stalk number and stalk diameter in sugarcane. However, the plants treated with diuron plus hexazinone presented lower stalk height. The herbicides diuron plus hexazinone, alone and in mixture with trifloxysulfuron plus ametryn, were efficient in the control of all morningglory and woodrose species. Application of trifloxysulfuron plus ametryn alone controlled satisfactorily only I. hederifolia. Metribuzin was efficient in the control of I. grandifolia, I. quamoclit, M. aegyptia and M. cissoides. Besides these species, the association of this herbicide with diuron plus hexazinone resulted in excellent I. hederifolia control. The mixture of metribuzin with trifloxysulfuron plus ametryn was efficient in controlling I. hederifolia, M. aegyptia and M. cissoides. The new emergence of the morningglory and woodrose species evaluated after herbicide application or manual weed elimination would not harm the mechanized harvest of sugarcane stalks in the next harvest.